2004
DOI: 10.1289/ehp.6481
|View full text |Cite
|
Sign up to set email alerts
|

Maternal stress modulates the effects of developmental lead exposure.

Abstract: Lead exposure is higher among children with low socioeconomic status (SES) compared with other children in the United States. Low SES itself is a known risk factor for various diseases and dysfunctions, effects that have been ascribed to chronic stress and associated elevation of glucocorticoids. Chronically elevated glucocorticoids and Pb provoke similar behavioral changes, and both can act on mesocorticolimbic systems of the brain. In this study we examined the hypothesis that these co-occurring risk factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
148
1
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(161 citation statements)
references
References 87 publications
11
148
1
1
Order By: Relevance
“…For example, studies have shown that maternal stressors, such as restraint stress, synergistically interact with diesel exhaust (Bolton et al 2013) and lead (Cory-Slechta et al 2004) to produce more profound effects in the offspring of pregnant rodents than either exposure alone. These relationships varied by offspring sex.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, studies have shown that maternal stressors, such as restraint stress, synergistically interact with diesel exhaust (Bolton et al 2013) and lead (Cory-Slechta et al 2004) to produce more profound effects in the offspring of pregnant rodents than either exposure alone. These relationships varied by offspring sex.…”
Section: Introductionmentioning
confidence: 99%
“…Adult male offspring demonstrated anxiety, significant memory deficits, and an increased neuroinflammatory response in the brain (e.g., decreased IL-10 levels) when co-exposed to diesel exhaust and stress during late pregnancy; female offspring of co-exposed dams showed only a slight increase in anxiety (Bolton et al 2013). Co-exposure to stress and prenatal lead was associated with changes in dopamine and corticosterone levels in female offspring in adulthood; in males, these exposures corresponded to increased impulsive choice behaviors (Cory-Slechta et al 2004). In the only study of stress as a modifier of pesticide exposure, Levin et al demonstrated that when maternal rat dams were stimulated with dexamethasone during gestation to elicit a stress response and offspring were exposed to chlorpyrifos, an OP pesticide, shortly after birth, the co-exposed offspring presented with greater hyperactivity, longer latency to begin feeding, and shorter feeding duration at 4–10 weeks after birth (adolescence and adulthood) compared to controls and to offspring exposed to chlorpyrifos alone.…”
Section: Introductionmentioning
confidence: 99%
“…One study has reported that environmental enrichment reversed the cognitive and molecular deficits induced by developmental lead exposure in rats (Guilarte, Toscano, McGlothan, & Weaver, 2003). Other studies have evaluated the interaction between 'environmental stress' and lead exposure on behavioural outcomes in rodents (Cory-Slechta, Virgolini, Thiruchelvam, Weston, & Bauter, 2004;Virgolini, Bauter, Weston, & Cory-Slechta, 2006;Virgolini et al, 2005;Virgolini, Volosin, Fulginiti, & Cancela, 2004). Finally, we have observed in the BMS that living in a neighbourhood with higher levels of psychosocial hazards (methods for neighbourhood psychosocial hazards scale in Glass et al, 2006) interacted with cumulative lead dose in associations with cognitive dysfunction.…”
Section: How Is Lead Dose Measured and What Does It Mean?mentioning
confidence: 99%
“…Long-term exposure to metals such as arsenic, cadmium, mercury, and lead by taking polluted water and foods increases a risk of chronic diseases (Cory-Slechta et al, 2004). Development of respiratory disorders, skin lesions, and carcinomata caused by arsenic poisoning is a well-known example to explain such risk (Bagla and Kaiser, 1996;Nordstrom, 2002).…”
Section: Introductionmentioning
confidence: 99%